2021
DOI: 10.1021/acs.iecr.0c06355
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrate Mesoporous Silica-Aluminosilicate Structure Improves Hydrogen Production via Methane Decomposition over a Nickel-Based Catalyst

Abstract: A potential nickel-supported infiltrate mesoporous silica-aluminosilicate (Ni/SAS) catalyst was developed for improving hydrogen production through methane decomposition reaction. Infiltrate mesoporous silica-aluminosilicate supports with different Si/Al ratios (25, 50, and 100) were synthesized through a sol–gel method, then nickel metal was loaded on the support using an incipient impregnation method. All SAS­(x) supports revealed a bimodal mesoporous structure with pore sizes at 2.7 and 3.9 nm. The aluminum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Most CNFs formed on the NiCu/MS(500) and NiCu/MS(800) catalysts through the base-growth mechanism, where the active Ni–Cu metals were partially covered by CNFs, , arising from a strong interaction between Ni–Cu and the MS support (in accordance with the H 2 -TPR results). Therefore, the activity and stability of both catalysts were deactivated during the reaction.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Most CNFs formed on the NiCu/MS(500) and NiCu/MS(800) catalysts through the base-growth mechanism, where the active Ni–Cu metals were partially covered by CNFs, , arising from a strong interaction between Ni–Cu and the MS support (in accordance with the H 2 -TPR results). Therefore, the activity and stability of both catalysts were deactivated during the reaction.…”
Section: Resultssupporting
confidence: 82%
“…Notably, the activity and stability of a Ni-based catalyst can be improved by selecting suitable supports and promoters because these supports have a substantial role in the catalytic reaction as they help to increase the metal catalyst dispersion and therefore, improve the activity of catalysts while minimizing the catalyst sintering. Many types of materials such as silica (SiO 2 ), alumina (Al 2 O 3 ), zeolite, and metal oxides, , such as ZrO 2 , MgO, and TiO 2 , have been used as catalyst supports for catalytic methane decomposition. SiO 2 material has been widely used as support because the interaction between metal and silica support is quite weak compared to the other supports in which the metal–support interaction is one of the factors determining the activity and lifetime of the catalyst. ,, Our previous work found that the SiO 2 structure support directly affected activity and stability in the methane decomposition reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the problem is that the active metal particles are easily encapsulated with carbon, causing a rapid deactivation of the catalyst. Therefore, many studies have been devoted to enhancing the catalyst performance 12‐20 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies have been devoted to enhancing the catalyst performance. [12][13][14][15][16][17][18][19][20] It has been indicated that the addition of a second metal to the nickel catalyst can improve the catalytic performance of CDM. 21 In this regard, Cu-promoted Ni catalysts have been widely investigated and demonstrated to enhance the catalytic life and carbon yield in CDM.…”
Section: Introductionmentioning
confidence: 99%